The Impact of Financial Constraints and Distress on Events after the Reporting Period in Accounting: Evidence from Türkiye - Bellikli, Uğur (Ekonomika, 2025)
The aim of this study is to examine the impact of leverage and debt cost which were substantiated as the factors of financial constraints, and the interest coverage ratio which was substantiated as financial distress of Turkish firms listed on the BIST MAIN Index on events after the reporting period. To achieve this aim, panel data analysis was conducted on 112 companies listed in the relevant index between 2014 and 2023. The dependent variable is disclosure after the reporting period, while the independent variables are leverage, cost of debt (financial constraints), and the interest coverage ratio (financial distress). The research findings show that high debt levels (particularly short-term debt) and financial distress increase the number of events after the reporting period. The findings can be interpreted as suggesting that Turkish firms experiencing financial constraints and distress may be more likely to engage in creative accounting practices to enhance the appearance of their financial statements.
Keywords: Accounting disclosure; Events after the Reporting Period; financial constraints and distress